Implications of alternative theories and practices of money on the Social and Solidarity Economy - Spanknebel, Wilhelm (2025)
The following text analyses the implications of alternative theories (and practices) of money on Social and Solidarity Economy. In the first part, the mainstream perception of money (commodity theory of money) is contrasted with the (chartalist) theories of credit-money and state-money, as well as the theory and practices of community currencies. Based on this analysis, the second part seeks to open up fields of discussion for Social and Solidarity Economy, particularly concerning concepts around the fundamental drivers of the dynamics of capitalist economic development and of community currencies.